Exploring factors influencing dental students' negative emotions during a gross anatomy laboratory in Taiwan - Po-Fang Tsai; Der-Yan Han (Elsevier, 2023)
Background/purpose: Negative emotions of medical students during a gross anatomy laboratory are documented in the field of medical education, but those of dental students are relatively less reported in the literature. The purpose of the present study was to explore negative emotions of dental students during the gross anatomy laboratory and possible influential factors. Materials and methods: Basic demographic variables, gross anatomy learning attitudes, and/or life attitudes were collected at five time points among year 2 dental students (n = 49) at a medical university in northern Taiwan. Multi-hierarchical regression analyses were executed to explore possible factors that led to negative emotions. Results: Students who were older, had more-positive attitudes towards life, and had more-positive attitudes towards the anatomy laboratory tended to have weaker negative emotions when they first faced the cadavers. Having a tendency to care about and help people and having a grateful attitude also significantly predicted weaker negative emotions at the middle and end of the semester, respectively. Conclusion: Negative emotions of younger dental students who first encounter a cadaver should be of concern. Striving to improve students' positive attitudes toward life, positive attitudes toward the gross anatomy laboratory, willingness to care about and help people, and an overall grateful attitude may help reduce negative emotions during the gross anatomy laboratory. At an institutional level, integrating educational activities that reduce negative emotions toward cadavers by dental students is highly recommended.